1999
DOI: 10.1164/ajrccm.160.4.9804075
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Respiratory Syncytial Virus and Adenovirus on Mononuclear Cell Cytokine Responses

Abstract: Respiratory syncytial virus (RSV) and adenovirus (Advs) serotype 3 (Adv3) and 7h (Adv7h) are associated with mild to severe respiratory infection and are indistinguishable during the acute phases of the illnesses. However, outcome and long-term prognosis are different with both infections. RSV infection is associated with later development of asthma, and Adv, mainly Adv7h, with severe lung damage, bronchiectasis, and hyperlucent lung. We hypothesized that this difference could be partly due to different immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 23 publications
3
28
0
1
Order By: Relevance
“…Previous studies demonstrated that IFN-c protein production did not increase in RSV infected peripheral blood MNCs. However, induction of IFN-c mRNA could be detected [18][19][20]. Therefore, the current study is generally consistent with these reports.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies demonstrated that IFN-c protein production did not increase in RSV infected peripheral blood MNCs. However, induction of IFN-c mRNA could be detected [18][19][20]. Therefore, the current study is generally consistent with these reports.…”
Section: Discussionsupporting
confidence: 92%
“…However, compared with other common upper respiratory tract infections such as adenovirus, rhinovirus, or influenza virus, RSV infection induces rather weak IFN-␥ responses (28,34,35). Increased severity of RSV infection is associated with decreased IFN-␥ levels in the airway (36,37).…”
mentioning
confidence: 99%
“…The affected lung is usually small as the infection during childhood inhibited the normal growth pattern, with secondary hypoplasia of the pulmonary artery. A number of reports have described SJS that followed some episodes in childhood, including radiation therapy, measles, pertussis, tuberculosis, foreign body, mycoplasma and viral infections, especially adenovirus (13)(14)(15)(16). The bronchoalveolar lavage from SJS patients presents a significant increase of neutrophils and a slight increase of lymphocytes, suggesting a hyperimmune reaction in the lung which may play a role in sustaining peripheral airway damage after the initial infection (17).…”
Section: A B Cmentioning
confidence: 99%